Chicken Embryo Malpositions and Deformities - Gary D. Butcher; Amir H. Nilipour (EDIS, 2003)
The objective of this study was to determine the relative incidences of malpositions and deformities, and their economic impacts. Major factors affecting their occurrence will be explained. Obviously, in any population it is anticipated to encounter malpositions and deformities during embryonic development. However, the incidence must be within accepted limits and changes must be made when excessive losses occur. This document is VM129, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 1, 2002.